Cover Jurnal Fitopatologi Vol. 19 No. 6, November 2023: Cover Jurnal Fitopatologi Vol. 19 No. 6, November 2023 - Editors Jurnal Fitopatologi Indonesia (Jurnal Fitopatologi Indonesia, 2023)
This editorial contains the front cover, editorial page, and back cover of the Jurnal Fitopatologi Vol. 19 No. 6, November 2023